2018
DOI: 10.1002/admi.201800263
|View full text |Cite
|
Sign up to set email alerts
|

Friction of Ionic Liquid–Glycol Ether Mixtures at Titanium Interfaces: Negative Load Dependence

Abstract: Our atomic force microscopy (AFM) experiments and non-equilibrium molecular dynamics (NEMD) simulations have demonstrated a negative friction-load dependence to ionic liquid-glycol ether mixtures, that is, the friction decreases as the normal load increases. NEMD simulations revealed a structural reorientation of the studied ionic liquid (IL): as the normal load increases, the cation alkyl chains of ILs change the orientation to preferentially parallel to the tip scanning path. The flat-oriented IL structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…Similar results are also found for tip on suspended graphene (12,13,16). In addition, a negative friction-load dependence is observed during the loading process for Si 3 N 4 tip sliding on titanium substrate with ionic liquidglycol ether mixtures in between as lubricant, which is resulted from the structural reorientation of the ionic liquid (9).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar results are also found for tip on suspended graphene (12,13,16). In addition, a negative friction-load dependence is observed during the loading process for Si 3 N 4 tip sliding on titanium substrate with ionic liquidglycol ether mixtures in between as lubricant, which is resulted from the structural reorientation of the ionic liquid (9).…”
Section: Introductionsupporting
confidence: 79%
“…This general trend has been confirmed by previous studies on various tribological systems (5,6). However, a few exceptions were observed recently, where counterintuitive examples were reported that the friction exhibited a complex dependence on normal load (7)(8)(9)(10)(11)(12)(13)(14)(15). In experiment, the friction of a nanoscale contact between an atomic force microscope (AFM) tip and chemically modified graphite or polymer-coated surfaces shows discrepancy for increasing (loading) and decreasing (unloading) normal loads (14,15).…”
Section: Introductionsupporting
confidence: 69%
“…The results of Shi et al [85] show that only the ionic liquid C6MIMBF4 with the long alkyl chain can obtain stable ionic liquids-based magnetic nanofluids which can be used as lubricant. An et al [86] found that the ionic liquid, glycol ether mixtures, at titanium interfaces had a negative friction load dependence, i.e., the friction force decreased with the increase of normal load. Han et al [87] discussed the activated slip and flow of ionic liquid lubricating molecules.…”
Section: Molecular Lubrication 2311 Ionic Liquid Lubricationmentioning
confidence: 99%
“…1a). An appearance of the a-Ti phase 48 in 0.1-1.0 Fe 3 O 4 + 0.1 FLG hybrid coatings was also observed in Fig. 2, attributed to the underlying Ti substrates, which is easily detected on thin-prepared coatings.…”
Section: Resultsmentioning
confidence: 54%